Gravitational Lensing for A Spherically Symmetric Regular Charged Black Hole in Weak Field Limit - Shidik, M. F.; Ramadhan, H. (Program Studi Fisika Universitas Negeri Jakarta, 2024)
Gravitational lensing is an integral part of the study of general relativity, as it is one of the direct consequences of general relativity. The existence of singularity within the black hole due to gravitational collapse is one of the key properties of the black hole. However, the introduction of non-linear electrodynamics (NLED) offers an intriguing possibility: nonsingular black holes. This work focuses on calculating the deflection angle within the weak field limit. Here, the photon's effective geometry associated with NLED is not incorporated; instead, the regular metric is utilized as it is, without presupposing its origins in NLED. A correction term in the deflection angle to the Reissner-Nordstrom (RN) case was found. This term manifests as a displacement in the position of the third image associated with the black hole.